Clinical management of blood-brain barrier disruptions after active raster-scanned carbon ion re-radiotherapy in patients with recurrent head-and-neck cancer - Held, Thomas; Akbaba, Sati; Uzun-Lang, Kristin; Harrabi, Semi B.; Bernhardt, Denise; Freudlsperger, Christian; Kargus, Steffen; Plinkert, Peter K.; Rieken, Stefan; Herfarth, Klaus; Debus, Jürgen; Adeberg, Sebastian (Cancers, 2019)
Purpose: The aim of the current evaluation was to assess central nervous system necrosis (CNSN) after re-irradiation with carbon ions (CR) in two-hundred seventeen (n = 217) patients with recurrent head-and-neck cancer (HNC). Methods: Thirty-six (n = 36) patients with CNSN were assessed retrospectively regarding clinical symptoms and radiographic response. Results: CNSN were classified according to clinical management in line with the Common Terminology Criteria for Adverse Events (CTCAE) v5.0. At a median follow-up of 25.3 months (range 3.3 - 79.9 months), the median time interval until occurrence of grade I, II, and III CNSN was 9.2 months (range 2.8 - 75.0 months), 10.2 months (range 2.3 - 60.5 months), and 16.6 months (range 8.7 - 32.5 months), respectively. In one patient with an adenocarcinoma infiltrating the frontal lobe, an extensive CNSN grade IV was suspected but the patient declined surgical intervention. Radiographic response after treatment of CNSN grade I, II, and III, defined as ≥25% reduction of the T2 alteration on Magnetic Resonance Imaging (MRI), was observed in 4 (16.0%), 5 (29.4%), and 4 (80%) patients, respectively. Conclusion: CNSN occurred late and frequent after re-irradiation with carbon ions in patients with HNC infiltrating the base of skull. The clinical outcome with adequate treatment was encouraging but correct diagnosis of CNSN remains challenging.
Gesehen am 28.05.2019